Single axis rotation pv solar panel tracking system - Ong, Horn Lu (2013)
A sustainable energy supply is required in Malaysia to meet the increasing electricity demand with rapid growing in population and economy. Photovoltaic solar panel is most suitable alternative way to generate electricity in Malaysia where most of its location receives large number of solar radiation throughout the year. However, fixed solar panel is more preferred than tracking panel because it is cost effective. In present work, the power output and efficiency of single-axis tracking solar panel is compared with fixed solar panel by experimentally in East Coast Malaysia. A single-axis tracking panel produces higher power output than fixed panel up to 28W. During this time, the average efficiency of tracking panel was about 66.70% and fixed panel was 39.96%. Hence, the percentage increment on average power output using tracking panel reached up to 66.92% compare to fixed panel during this period. The tracking panel module efficiency was higher than fixed panel for the same period and can reach up to 28.9% at 6.00p.m. In conclusion, single-axis tracking panel is more efficient than fixed panel in premeridian and postmeridian. Thus, it produces higher power output than fixed panel which means it utilize the most of available solar radiation effectively and this will reduce payback period of the initial investment cost.